Docetaxel, oxaliplatin, 5FU, and trastuzumab as first-line therapy in patients with human epidermal receptor 2-positive advanced gastric or gastroesophageal junction cancer: Preliminary results of a phase II study. Issue 20 (May 2018) - Roviello, Giandomenico; Petrioli, Roberto; Nardone, Valerio; Rosellini, Pietro; Multari, Andrea Giovanni; Conca, Raffaele; Aieta, Michele
Abstract : Abstract: The aim of this study is to report first preliminary results of patients enrolled in a phase II study that will investigate the activity and safety of docetaxel, oxaliplatin, and 5-fluorouracil (DOF) in combination with trastuzumab in human epidermal receptor-2 (HER-2) positive patients with advanced gastric or gastroesophageal junction (GEJ) cancer. Treatment consisted of docetaxel 70 mg/m 2 combined with oxaliplatin 130 mg/m 2 on day 1, and continuous infusion 5-fluorouracil mg/m 2 days 1–5 plus trastuzumab at the standard dose on day 1, every 3 weeks for a maximum of 8 cycles. Fifteen patients were enrolled. The overall response rate was 60%. The median progression-free survival was 9.2 months (95% confidence interval [CI], 4.4–10.1 months) and the median overall survival was 19.4 months (95% CI, 8.9–21.1 months). Grade 3 neutropenia was observed in 3 patients (20%). The DOF plus trastuzumab seems active in HER-2 positive advanced gastric or GEJ cancer, final results of the phase II study are awaited. Abstract : Supplemental Digital Content is available in the text